2016
DOI: 10.3354/dao02975
|View full text |Cite
|
Sign up to set email alerts
|

Filling a gap in the distribution of Batrachochytrium dendrobatidis: evidence in amphibians from northern China

Abstract: Chytridiomycosis caused by Batrachochytrium dendrobatidis (Bd) has been recognized as a major driver of amphibian declines worldwide. Central and northern Asia remain as the greatest gap in the knowledge of the global distribution of Bd. In China, Bd has recently been recorded from south and central regions, but areas in the north remain poorly surveyed. In addition, a recent increase in amphibian farming and trade has put this region at high risk for Bd introduction. To investigate this, we collected a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Bd is responsible for the decline of at least 500 amphibian species in Australia, Central America, South America, the Sierra Nevada in North America, and the Iberian Peninsula in Europe. 38 , 39 Native Asian amphibians generally show no clinical signs of chytridiomycosis and a low Bd prevalence, 28 , 40 , 41 , 42 , 43 with no declines in Asian amphibians reported. 38 , 44 The mass mortality of wild American bullfrogs at Finley Lake in the US was attributed to chytridiomycosis, and experimental evidence shows that bullfrogs were susceptible to Bd (one strain).…”
Section: Discussionmentioning
confidence: 94%
“…Bd is responsible for the decline of at least 500 amphibian species in Australia, Central America, South America, the Sierra Nevada in North America, and the Iberian Peninsula in Europe. 38 , 39 Native Asian amphibians generally show no clinical signs of chytridiomycosis and a low Bd prevalence, 28 , 40 , 41 , 42 , 43 with no declines in Asian amphibians reported. 38 , 44 The mass mortality of wild American bullfrogs at Finley Lake in the US was attributed to chytridiomycosis, and experimental evidence shows that bullfrogs were susceptible to Bd (one strain).…”
Section: Discussionmentioning
confidence: 94%
“…Our study suggests that the alien P. nigromaculatus on the TP stemmed from Chongqing. A previous study found that the amphibian chytrid fungus Batrachochytrium dendrobatidis ( Bd ) ( Zhu et al 2014 , 2016 ), which is a lethal pathogen responsible for declines in amphibians worldwide, was detected in P. nigromaculatus in Chongqing. Furthermore, Bd has been found in other regions of high elevations, such as the Andes ( Seimon et al 2007 ), the Rocky Mountains ( Pilliod et al 2010 ), and the Sierra Nevada ( Vredenburg et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Skin mucus has been collected from amphibians [111,[149][150][151][152][153][154][155] and fish [156][157][158]. In amphibians, the main focus of studies utilising skin mucus has been the detection of the fungal pathogen Batrachochytrium dendrobatis [111,150,151,[153][154][155]; however, wider investigations of the skin microbiome [149] and cortisol detection [152] are further uses for this material. The sensitivity of pathogen detection in skin mucus may be limited when the intensity of infection is low [151].…”
Section: Saliva and Other Body Fluidsmentioning
confidence: 99%